Intentionality, intersubjectivity, and education : A study in the philosophy of Bernard Lonergan - McDermott, Seán (Trinity College (Dublin, Ireland). School of Education, 2007)
This study seeks to establish the following three aims which are set out in the introduction: -- 1) To examine the relevance of Lonergan’s theories as a foundation for a comprehensive philosophy and theoretical model of the educational process; -- 2) To explore the possibility of a practical pedagogical method based on such a model or philosophy, and particularly on the ‘self-appropriation of cognitive interiority’ which is an integral part of it; and, Apart from Lonergan’s own method of ‘self-appropriation of inferiority’, the other method of ‘proof’ adopted by this study has been described as ‘the method of converging theories’. This is the preferred method of Jean Piaget, and such a method necessarily entails a synthesis, a ‘grand scheme’, a bringing together and collating of the theories of many different philosophers, psychologists, and educationalists. By demonstrating the convergence’ or compatibility of Lonergan’s inisights with these theories, the study attempts to establish the validity of these same insights, bearing ini mind that, strictly speaking, “proof is a concept that should be restricted to closed systems, such as rmathematics.”
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin